Nurses’ perspectives on injection devices for controlled ovarian stimulation in in-vitro fertilisation: a cross-sectional survey from the GCC countries - Elhakim, El Samawal; Fouad, Alaa; Alorf, Mansour; Al Saadoun, Alyah; Detho, Sajida (Frontiers in Endocrinology, 2026)
IntroductionThe design and functionality of injection devices for controlled ovarian stimulation (COS) significantly influence dose accuracy and patient comfort, affecting adherence and treatment success. This study explores the perspectives of couple infertility nurses from the Gulf Council Cooperation (GCC) countries on COS injection devices and their impact on patient experience and adherence.Materials and methodsA cross-sectional, multicentre, quantitative study was conducted among couple infertility nurses from high- and low-volume assisted reproductive technology (ART) clinics in the United Arab Emirates (UAE) and Kuwait. A structured survey was used to assess nurses’ views on three injection modalities: pre-filled injection pens, syringes/vials, and the COMBO regimen (interchangeable use of pens and vials).ResultsForty-two nurses were included. The participants perceived the pre-filled pens as easier to use, more convenient, and quicker to teach than syringes. Training time for pre-filled pen use was predominantly less than ten minutes, with 48% requiring under five minutes and 52% requiring under ten minutes. In contrast, training on vial and syringe use was more time-consuming; only 14% reported taking under ten minutes, 55% required 5–10 minutes, and 31% took more than ten minutes. Compared to the COMBO regimen, 96% found the pen easier to teach and faster to train on, and 100% expressed confidence in patients’ ability to self-administer correctly. Satisfaction with the pre-filled pen was high, with 95% and 96% of nurses satisfied or very satisfied when compared to syringes and the COMBO regimen, respectively. A majority (91%) recommended the pen as their first choice or most frequent recommendation. Additionally, nurses perceived lower clinic traffic and fewer errors with the pen, indicating potential economic and safety benefits.ConclusionThis exploratory, descriptive survey suggests that nurses in couple infertility centres in the GCC region perceive multidose pre-filled pens as easier to use and teach than traditional syringes or COMBO regimens.